2008
DOI: 10.1111/j.1530-0277.2008.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Risk Factors for Fetal Alcohol Syndrome and Partial Fetal Alcohol Syndrome in South Africa: A Third Study

Abstract: Maternal data in this population are generally consistent with a spectrum of effects exhibited in the children. Variation within the spectrum links greater alcohol doses with a greater severity of effects among children of older and smaller mothers of lower socio economic status in their later pregnancies. Prevention is needed to address known maternal risk factors for FASD in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
210
2
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(224 citation statements)
references
References 84 publications
6
210
2
4
Order By: Relevance
“…In general, the factors associated with AEP risk in the present study are consistent with the maternal risk factors for FAS identified in previous studies in the Western and Northern Cape Provinces (May et al, 2005(May et al, , 2008Urban et al, 2008;Viljoen et al, 2002). However, parity was associated with lower risk of an AEP in this survey, but is usually associated with greater risk of having a child with an FASD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, the factors associated with AEP risk in the present study are consistent with the maternal risk factors for FAS identified in previous studies in the Western and Northern Cape Provinces (May et al, 2005(May et al, , 2008Urban et al, 2008;Viljoen et al, 2002). However, parity was associated with lower risk of an AEP in this survey, but is usually associated with greater risk of having a child with an FASD.…”
Section: Discussionsupporting
confidence: 92%
“…Maternal risk factors for FAS have been investigated in the Western and Northern Cape provinces (May et al, 2005(May et al, , 2008Urban et al, 2008;Viljoen, Croxford, Gossage, Kodituwakku, & May, 2002). The risk factors identified by those studies include: (1) demographic characteristics (e.g., education, occupation/employment, income, marital status at index pregnancy); (2) alcohol consumption patterns (e.g., current drinking, age of onset of drinking); (3) tobacco use behaviours (e.g., tobacco use during pregnancy); (4) partners' and family members' characteristics (e.g., partner drinking, heavy drinking by family members); (5) alcohol consumption prior to and during each month of the past pregnancy; (6) reproductive health history (e.g., parity, gravidity, birth order of index child, stillbirth); (7) physical characteristics (e.g., height, weight and body mass index; BMI).…”
mentioning
confidence: 99%
“…[42][43][44] Current alcohol consumption for the week preceding the interview was embedded into the nutrition questions 45 to aid accurate calibration of drinking quantity, frequency, and timing of alcohol use before and during the index pregnancies. 10,11,[23][24][25]33 Retrospective reports of alcohol use have been found to be superior to concurrent reports, but alcohol use has still been found to be frequently underreported in studies such as this. 33,[46][47][48] Maternal risk data were gathered for 153 women (Fig 2).…”
Section: Study Procedures: Screening In Tiers I and Iimentioning
confidence: 88%
“…Detailed maternal risk factor information for FASD in other populations has been reported elsewhere. 12,24,25,34,46 …”
Section: Study Procedures: Screening In Tiers I and Iimentioning
confidence: 99%
See 1 more Smart Citation